On the impact of user segmentation and behaviour analysis over traffic generation in beyond 4G networks - Gonçalves, L. (2017)
In this paper, a survey of the mobile data traffic growth over the last decade is performed, showing historically how data consumption patterns have evolved. Based on the results from the survey and the most important factors for unprecedented traffic growth from last years, a set of user-centric services and scenarios are identified as the most prevalent by 2020. Based on service characteristics and subscribers' behaviour and consumption regarding traffic generation, four user segments are derived. All these factors allow introducing an impact model that characterises user segment's behaviour over post-4G cellular networks, namely, its consistency and stability towards traffic generation, data consumption and service usage, providing mobile network operators with relevant information to predict user segment dispersion, stability and risk. Real and estimated market data are used to test the impact model, and most relevant results are shown. Overall, the proposed impact model aims to bring together technological, sociological and also economical perspectives into a single analytical framework, meeting both mobile network operators and subscriber's expectations of high quality of service with continuous cost decrease.